Pengaruh Return On Assets (ROA) dan Return On Equity (ROE) terhadap Harga Saham pada Perusahaan Go Public yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019 - Khairul Anwar Lubis; Emelia Rahmadhany Putri Gami (Jurnal Bisnis, Manajemen, dan Akuntansi, 2022)
This study aims to (1) determine the effect of Return On Assets (ROA) on Stock Prices Listed on the Indonesia Stock Exchange (IDX). (2) To determine the effect of Return On Equity (ROE) on the price of shares listed on the Indonesia Stock Exchange (IDX). Collecting data in this study using secondary data obtained from literature studies and documentation through the Indonesia Stock Exchange (IDX). The conclusions in this study are as follows: Return on Assets has a partially negative and significant effect on stock prices in Go Public Companies Listed on the Indonesia Stock Exchange (IDX) in 2019. This means that the higher the ROA, the lower the stock price. Return On Equity has a positive and significant partial effect on stock prices in Go Public Companies Listed on the Indonesia Stock Exchange (IDX) in 2019. This can be interpreted that the higher the ROE, the higher the stock price. Return On Assets and Return On Equity simultaneously have a significant effect on stock prices in Go Public Companies Listed on the Indonesia Stock Exchange (IDX) in 2019. This can be interpreted that the higher the profitability value, the higher the stock price value. Keywords : Return On Assets (ROA), Return On Equity (ROE), Stock Price, Indonesia Stock Exchange.